The Analysis of Performance Reliability Electric Power System in 20 Kv Distribution Network in PT. PLN - Mendrofa, Silviharyani; Dalimunthe, Muhammad Erpandi; Rahmaniar, Rahmaniar (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2025)
The reliability of the electric power distribution system plays a crucial role in ensuring a stable and continuous power supply to consumers. This study analyzes the performance reliability of the 20 kV distribution network at PT. PLN (Persero) UP3 North Medan by evaluating key reliability indices, including SAIDI (System Average Interruption Duration Index), SAIFI (System Average Interruption Frequency Index), and CAIDI (Customer Average Interruption Duration Index). The research methodology involves data collection from historical outage records, fault analysis, and statistical evaluation of reliability indices. The findings indicate that the reliability performance of the 20 kV distribution network in UP3 North Medan is influenced by various factors, such as equipment failures, weather conditions, and external disturbances. Based on the analysis, strategies for improving reliability are proposed, including preventive maintenance, network automation, and enhanced fault detection systems. By implementing these measures, PLN can improve service quality and reduce power outages, ultimately enhancing customer satisfaction and system efficiency.